Analysis of Fulfillment of Facilities and Infrastructure Based on National Education Standards at Elementary Education Institutions (RA/TK and SD/MI) - Arafah, Muhammad Yasir; Azizah, Hafidzotul; Maesaroh (Proceeding International Conference on Religion, Science and Education, 2022)
The fulfillment of adequate educational infrastructure and in accordance with national education standards is a requirement that must be met as a supporting factor for the implementation of quality school learning programs and processes. Lack of fulfillment of infrastructure standards will have an impact on the low educational environment resources. This study aims to identify and describe the fulfillment of infrastructure standards based on the Regulation of the Minister of National Education of the Republic of Indonesia No. 24 of 2007 concerning Standards of Facilities and Infrastructure for Elementary Schools/Madrasah Ibtidaiyah (SD/MI) and Minister of Education and Culture of the Republic of Indonesia No. 137 of 2014 concerning National Standards for Early Childhood Education. The object of this research is at elementary level educational institutions, namely TK Aisyiyah Bustanul Athfal Sapen, Madrasah Ibtidaiyah Negeri 1 Yogyakarta, and SD Muhammadiyah Condongcatur Sleman.The research method used is a descriptive qualitative approach with analytical methods. The data analysis technique in this research is triangulation of data derived from primary data sources of observation, documents, interviews and documentation. The results obtained are that the overall infrastructure at Elementary Education Institutions (RA and MI) with (1) the condition of facilities and infrastructure in these educational institutions can be categorized as adequate and complete in supporting the process of school activities and teaching and learning processes (2) supporting factors in fulfilling infrastructure facilities come from the procurement of funds and management of existing infrastructure facilities, (3) the inhibiting factor in the fulfillment of infrastructure facilities at the basic level educational institutions is in terms of the lack of funds with the required infrastructure.